3D Ion‐Conducting, Scalable, and Mechanically Reinforced Ceramic Film for High Voltage Solid‐State Batteries. (25th June 2020) - Kim, Hyun Woo; Han, Jinhyup; Lim, Young Jun; Choi, YunSeok; Lee, Eungje; Kim, Youngsik
Abstract: Concerning the safety aspects of Li + ion batteries, an epoxy‐reinforced thin ceramic film (ERTCF) is prepared by firing and sintering a slurry‐casted composite powder film. The ERTCF is composed of Li + ion conduction channels and is made of high amounts of sintered ceramic Li1+ x Ti2‐ x Al x (PO4 )3 (LATP) and epoxy polymer with enhanced mechanical properties for solid‐state batteries. The 2D and 3D characterizations are conducted not only for showing continuous Li + ion channels thorough LATP ceramic channels with over 10 −4 S cm −1 of ionic conductivity but also to investigate small amounts of epoxy polymer with enhanced mechanical properties. Solid‐state Li + ion cells are fabricated using the ERTCF and they show initial charge–discharge capacities of 139/133 mAh g −1 . Furthermore, the scope of the ERTCF is expanded to high‐voltage (>8 V) solid‐state Li + ion batteries through a bipolar stacked cell design. Hence, it is expected that the present investigation will significantly contribute in the preparation of the next generation reinforced thin ceramic film electrolytes for high‐voltage solid‐state batteries. Abstract : An epoxy‐reinforced thin ceramic film (ERTCF) is prepared by firing and sintering a slurry‐casted composite powder film. The ERTCF is composed of Li + ion conduction channels and is made of high amounts of sintered ceramic Li1+ x Ti2− x Al x (PO4 )3 and epoxy polymer with enhanced mechanical properties for solid‐state batteries.